Konseling Kelompok Dengan Pendekatan Eksistensial untuk Meningkatkan Kebermaknaan Hidup Orang Dengan HIV-AIDS (ODHA) - Alma Yulianti (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2020)
Abstract. Group counseling with an approach focused on self-existence or better known as existentialism helps individuals to get back to their functions, meanings and awareness. This approach is based on the philosophy of existentialism not only on a substantial basis but also in various therapeutic processes. The existentialism approach seeks to understand the nature and essence of human beings as individuals in the world. On the other hand humanism elevates personal values, dignity and individual dignity and occupies a central position in daily life. Human Immuno Deficiency Virus is a virus that is capable of disrupting the human body's immune system and resulting in the onset of AIDS. The meaningfulness of life sought after experienced by each individual will experience a process that is not the same because there is a uniqueness in each individual, one of whom is a person with HIV-AIDS. This article examines the concept of self-existence based on a humanistic existential approach and focuses on the individual person in increasing the meaningfulness of Life of People with HIV AIDS.Keywords: group counseling, existential approach, meaning of life, people with HIV/AIDS.